Конституціоналізація процесу європейської інтеграції України. - Чернопищук, Яна Володимирівна; Чернопищук, Яна Владимировна; Chernopyshchuk, Yana V. (My University, 2013)
Дисертація на здобуття наукового ступеня кандидата юридичних наук за спеціальністю 12.00.02 – конституційне право, муніципальне право – Національний університет «Одеська юридична академія», Одеса, 2013. У дисертації здійснено комплексне дослідження теорії та практики конституціоналізації процесу європейської інтеграції України. Уперше в науці конституційного права України визначено поняття «конституціоналізація процесу європейської інтеграції України», а також сформовано його науково-практичну парадигму. На підставі дослідженої конституційної доктрини та європейської практики зі здійснення конституціоналізації розкрито етимологію терміна «конституціоналізація», всебічно розглянуто доктринальні підходи до розуміння конституціоналізації ЄС, установлено елементи, ознаки, передумови здійснення конституціоналізації процесу європейської інтеграції держави. За результатами дослідженого досвіду конституційних перетворень у країнах-членах ЄС під впливом наднаціональних (квазі-конституційних) властивостей норм права ЄС та проаналізованих українських сучасних конституційно-правових реалій процесу євроінтеграції розроблено пропозиції щодо напрямків та змісту конституціоналізації процесу європейської інтеграції України.

Диссертация на соискание научной степени кандидата юридических наук по специальности 12.00.02 – конституционное право, муниципальное право – Национальный университет «Одесская юридическая академия», Одесса, 2013. В диссертации осуществлено комплексное исследование теории и практики конституционализации процесса европейской интеграции Украины. Впервые в науке конституционного права Украины определено понятие «конституционализация процесса европейской интеграции Украины», а также сформирована его научно-практическая парадигма.На основании исследованной конституционной доктрины и европейской практики осуществления конституционализации раскрыта этимология термина «конституционализация», всесторонне рассмотрены доктринальные походы к пониманию конституционализации Европейского Союза, установлены элементы, признаки, условия осуществления конституционализации процесса европейской интеграции государства. В результате изученного опыта конституционных преобразований в государствах-членах ЕС под воздействием наднациональных (квази-конституционных) свойств норм права ЕС и проанализированных современных украинских конституционно-правовых реалий процесса евроинтеграции разработаны предложения относительно направлений и содержания конституционализации процесса европейской интеграции Украины.

Thesis for a scientific degree of Master of Legal Science, specialty 12.00.02 – constitutional law; municipal law – National University «Odessa Law Academy», Odessa, 2013. The thesis presents itself as a comprehensive research on theory and practice of the constitutionalisation of the European integration process of Ukraine. The research is focused on the cognition of the phenomenon of constitutionalisation of the European integration process, analysis of its realization in the EU Member States and determination of perspective directions for Ukraine’s way of the constitutionalisation of European integration. The object of the research referred to an elaboration of scientific and practical paradigm of the constitutionalisation of European integration process regarding the experience of constitutional amendments held in the EU Member States. The process of integration into the EU means that the countries shall comply with the rule of law within the Union. Being a basic principle of the EU, the rule of law means that any activity is grounded on Treaties, voluntarily and democratically agreed by all member countries. In order to meet the requirement on binding execution of the main EU agreements the countries are faced with approximation of domestic legislation to the EU law and impact of supranational legal power of the EU legal acts on national legislation. The first has to be performed in order to ensure the correspondence of interior legal provisions to the EU legal standards (which further enable the unanimous execution of EU law in all countries) and the second – provides unconditional application of binding EU legal acts in each Member State without regard for the prescription on relevant matter in national legal acts, including Constitution. Integrating countries shall recognise and respect the core values of the EU – human dignity, freedom, democracy, equality, the rule of law and respect for human rights, – which are usually fixed in constitutions of states, because of their fundamental character. Considering the supremacy of constitution in national legal system guaranteeing the stability and sovereignty of interior legal order the actual problem raises in defining of measures and directions of amending constitutions during European integration, which have to be specified for each certain country. The necessity to change the constitution was equally fair for both countries-founders and countries of last wave of enlargement due to signing of the Treaty of Lisbon. Particular approaches of the interpretation of domestic legislation in compliance with the EU law should be elaborated by state authorities on constitutional jurisdiction. The complexity of European integration influences on substance and spirit of national constitution and results in «constitutionalisation of European integration of the country». It was established that the current constitutional process in EU countries occurred under the influence of the EU law. It is possible to imagine the constitutionalisation phenomenon in two reversible dimensions where meaning of constitutionalisation will differ respectfully. The first is a common known in European doctrine process of consolidation of national constitutional gains aimed on final creation of constitutional act possessing the supranational (prior) legal effect – up-directed process. The second understanding of the constitutionalisation presentes a reverse effect of the abovementioned consolidation and mean the influence of constitutional acts of supranational organization on the national constitutions – down-directed. Both tendencies of process are possible only during European integration and dynamic transformations within the legal orders interaction, which is like common reason for two dimensions of constitutionalisation. For the first time the Ukrainian constitutional law science was enriched with a notion of the «constitutionalisation of the European integration process of Ukraine» and its scientific and practical paradigm. Within the research of the etymology of the term «constitutionalisation» was learnt and the doctrines of the understanding of constitutionalisation within the EU were comprehensively considered. On the basis of explored theory and practice of the constitutionalisation of European integration process the author determined elements, features, circumstances of its realization. It was established and emphasized that judgments of constitutional courts serve as a legal ground for making amendments into the constitution for execution of legal demands of the EU in case of their contradiction to national constitutional provisions, but at the same time they serve as an instrument for upholding national constitutional interests and priority of internal constitutional legislation during the process of European integration. Results of the research on the experience of constitutional transformations in the EU member-states influenced by supranational (quasi-constitutional) features of European Law and analysis of modern Ukrainian constitutional legal realities of the European integration process enable to elaborate the proposals on the directions and contents of the constitutionalisation of the European integration process of Ukraine. Key words: European integration, European Union, EU law, supranationality, constitutionalisation of the European integration process, constitution of Ukraine, legal values, rule of law, Constitutional Court of Ukraine, national identity, constitutional transformation.
Чернопищук Я. В. Конституціоналізація процесу європейської інтеграції України. : автореф. дис. ... канд. юрид. наук : 12.00.02 / Я. В. Чернопищук; кер. роботи А. Р. Крусян; Нац. ун.-т "Одеська юридична академія". – Одеса, 2013. – 22 с.
Keywords: європейська інтеграція; Європейський Союз; право ЄС; наднаціональність; конституціоналізація процесу європейської інтеграції; конституція України; правові цінності; верховенство права; Конституційний Суд України; національна ідентичність; конституційна реформа; европейская интеграция; Европейский Союз; право ЕС; наднациональность; конституционализация процесса европейской интеграции; конституция Украины; правовые ценности; верховенство права; Конституционный Суд Украины; национальная идентичность; конституционная реформа; European integration; European Union; EU law; supranationality; constitutionalisation of the European integration process; constitution of Ukraine; legal values; rule of law; Constitutional Court of Ukraine; national identity; constitutional transformation